ANALYSIS OF PREFERENCES AND PATTERNS OF MILLENNIAL TRAVELERS TO BALI - Ni Ketut Wiwiek Agustina (JURNAL KEPARIWISATAAN, 2018)
Currently more than 45% of the population in Asia are millennial generation. So as with the tourists who are mostly from the millennial generation. Millennial tourist grows in a practical environment and everything used the internet. Millennial tourists use the internet to book a trip or some ticket. It can be easier to take some trip to different places. Jakarta is the capital city of Indonesia. This metropolitan area is the largest urban areas in Indonesia even in Southeast Asia. Jakarta travelers will travelling many times and come back to the same place that made a beautiful memory. With the existence of this research know about the preferences and patterns of the trip of Jakarta millennial tourists to Bali. The method using accidental sampling by interviewing the respondent directly. The results of the research that have been conducted on millennial tourists is the high interest of millennial tourists in Jakarta to Bali is influenced by the easiest facilities to reach the internet, the number of places that have unique and popular places to take pictures and also there are many places that millennial tourists can explore according to the characteristics millennial tourists.